Dermatomicosis superficiales: cuando el diagnóstico lo entrega la histología - Manubens V, Víctor; Araya B, Irene; Morales H, Claudia; Carreño T, Laura (Revista Hospital Clínico Universidad de Chile, 2021)
Superficial dermatomycosis are prevalent pathologies in the medical field and their diagnosis is fundamentally clinical. Histopathology is not considered part of his study, however, the diagnosis is exceptionally obtained by biopsy, when dermatomycosis was not suspected. Unpublished retrospective work is carried out on patients who had the histopathological diagnosis of superficial dermatomycosis between the years 2000-2019 at the HCUCH, based on selection criteria, obtaining 19 patients, in which the following were analyzed: age, gender, clinical characteristics, location, presumptive diagnosis and mycological and histological examinations. He stressed, as was our hypothesis, that dermatomycosis was not clinically suspected, since the presumptive diagnoses were various dermatoses. The most suspected dermatosis was psoriasis, as a result that 57.8% of the dermatoses studied had erythematous scaly plaques on examination. Another relevant fact is that only 21% of the cases underwent a direct mycological prior to the biopsy, which was negative (‘’ false negative’’). It is concluded, then, that superficial dermatomycosis should be considered clinical simulators of other dermatoses, so clinical suspicion and support of mycological examination and fungal culture is essential.